2021
DOI: 10.1016/j.kint.2021.02.040
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter randomized controlled trial indicates that paclitaxel-coated balloons provide no benefit for arteriovenous fistulas

Abstract: Complications of vascular access are an important cause of morbidity and mortality in hemodialysis patients. 1 It is widely accepted that an arteriovenous fistula (AVF) is the optimal form of vascular access, with better patency and lower infection rates than arteriovenous grafts and central

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…However, a recent trial revealed a contrasting outcome. In 2021, the paclitaxel-coated balloons and angioplasty of AV fistulas (PAVE) trial was conducted with 212 randomized patients [14]. Time to loss of TLPP with DCB was not significantly different from that with the standard balloon (hazard ratio (HR), 1.18; 95% confidence interval (CI), 0.78-1.79; p = 0.440) [14].…”
Section: Effectiveness Of Dcbs In Preventing Restenosis Of Arteriovenous Access According To Randomized Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent trial revealed a contrasting outcome. In 2021, the paclitaxel-coated balloons and angioplasty of AV fistulas (PAVE) trial was conducted with 212 randomized patients [14]. Time to loss of TLPP with DCB was not significantly different from that with the standard balloon (hazard ratio (HR), 1.18; 95% confidence interval (CI), 0.78-1.79; p = 0.440) [14].…”
Section: Effectiveness Of Dcbs In Preventing Restenosis Of Arteriovenous Access According To Randomized Controlled Trialsmentioning
confidence: 99%
“…In 2021, the paclitaxel-coated balloons and angioplasty of AV fistulas (PAVE) trial was conducted with 212 randomized patients [14]. Time to loss of TLPP with DCB was not significantly different from that with the standard balloon (hazard ratio (HR), 1.18; 95% confidence interval (CI), 0.78-1.79; p = 0.440) [14]. One possible explanation for the contrasting result between the PAVE and IN.PACT trials is that the trials used different treatment balloons with different drug doses, although this does not refer to the actual doses that reached the target.…”
Section: Effectiveness Of Dcbs In Preventing Restenosis Of Arteriovenous Access According To Randomized Controlled Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4 RCTs were identi ed and included in the meta-analyses, with 956 participants (11)(12)(13)(14). An overview of the study ow of the selection process is presented in Fig.…”
Section: Included Studiesmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) that compared DCB angioplasty with conventional balloon angioplasty for the treatment of dysfunctional hemodialysis vascular access with a larger sample size have been published (11)(12)(13)(14). Results of these trials were less consistent and led to an ongoing debate on whether DCB angioplasty could indeed improve outcomes.…”
Section: Introductionmentioning
confidence: 99%